The Association of Depressive Symptoms With Brain Volume Is Stronger Among Diabetic Elderly Carriers of the Haptoglobin 1-1 Genotype Compared to Non-carriers - Livny, Abigail; Schnaider Beeri, Michal; Heymann, Anthony; Schmeidler, James; Moshier, Erin; Tzukran, Ruth; Tsarfaty, Galia; Leroith, Derek; Preiss, Rachel; Soleimani, Laili; Guerrero-Berroa, Elizabeth; Silverman, Jeremy M.; et al. (Frontiers in Endocrinology, 2019)
AIM: Depression is highly prevalent in type 2 diabetes and is associated with lower adherence to medical treatments, worse glycemic control and increased risk for diabetes-related complications. The mechanisms underlying depression in type 2 diabetes are unclear. The haptoglobin (Hp) genotype is associated with type 2 diabetes related complications including increased risk for cerebrovascular pathology and worse cognitive performance. Its relationship with depression is unknown. We investigated the role of Hp genotype on the association of depression with brain and white matter hyperintensities (WMH) volumes. METHODS: Depressive symptoms (measured with the 15-item Geriatric Depression Scale), brain MRI, and Hp genotypes, were examined in elderly subjects with type 2 diabetes [29 (13.8%) Hp 1-1 carriers and 181 (86.2%) non-carriers]. The interaction of Hp genotype with number of depressive symptoms on regional brain measures was assessed using regression analyses. RESULTS: The significant interactions were such that in Hp 1-1 carriers but not in non-carriers, number of depressive symptoms was associated with overall frontal cortex (p=0.01) and WMH (p=0.04) volumes but not with middle temporal gyrus volume (p=0.43). CONCLUSIONS: These results suggest that subjects with type 2 diabetes carrying the Hp 1-1 genotype may have higher susceptibility to depression in the context of white matter damage and frontal lobe atrophy. The mechanisms underlying depression in diabetes may differ by Hp genotype.